Synergistic Effect of Quinic Acid Derived From Syzygium cumini and Undecanoic Acid Against Candida spp. Biofilm and Virulence - Muthamil, Subramanian; Balasubramaniam, Boopathi; Balamurugan, Krishnaswamy; Pandian, Shunmugiah Karutha (Frontiers in Microbiology, 2018)
In recent decades, fungal infections have incredibly increased with Candida genus as the major cause of morbidity and mortality in hospitalized and immunocompromised patients. Most of the Candida species are proficient in biofilm formation on implanted medical devices as well as human tissues. Biofilm related Candida infections are very difficult to treat using common antifungal agents owing to their increased drug resistance. To address these issues, the present study investigated the antibiofilm and antivirulent properties of Syzygium cumini derived quinic acid in combination with known antifungal compound undecanoic acid. Initially, antibiofilm potential of S. cumini leaf extract was assessed and the active priniciples were identified through gas chromatography and mass spectrometry analysis. Among the compounds identified, quinic acid was one of the major compounds. The interaction between quinic acid and undecanoic acid was found to be synergistic in the Fractional inhibitory concentration index (≤ 0.5). Results of in vitro assays and gene expression analysis suggested that the synergistic combinations of quinic acid and undecanoic acid significantly inhibited virulence traits of Candida spp. such as the biofim formation, yeast-to-hyphal transition, extracellular polymeric substances production, filamentation, secreted hydrolases production and ergosterol biosynthesis. In addition, result of in vivo studies using Caenorhabditis elegans demonstrated the nontoxic nature of QA-UDA combination and antivirulence effect against Candida spp. For the first time, synergistic antivirulence ability of quinic acid and undecanoic acid was explored against Candida spp. Thus, results obtained from the present study suggest that combination of phytochemicals might be used an alternate therapeutic strategy for the prevention and treatment of biofilm associated candida infection.